EUCALYPTUS GALL WASP, Leptocybe invasa FISHER & LASALLE (HYMENOPTERA: EULOPHIDAE) IN BRAZIL: NEW FOREST PEST REACHES THE NEW WORLD - Costa, Valmir Antonio; Berti Filho, Evoneo; Wilcken, Carlos Frederico; Stape, JosÃ© Luiz; LaSalle, John; Teixeira, Liliane de Diana (REVISTA DE AGRICULTURA, 2015)
EUCALYPTUS GALL WASP, Leptocybe invasa FISHER & LASALLE (HYMENOPTERA: EULOPHIDAE) IN BRAZIL: NEW FOREST PEST REACHES THE NEW WORLD